Temporary course of fluoxetine and norfluoxetine in German Shepherd and Akita Inu dogs - Tapia Araya, Christian Marcelo (2020)
The pharmacokinetics of fluoxetine were evaluated in two phylogenetically distant dog breeds. The quantification method was fine-tuned and validated through the mean, standard deviation and coefficient of variation (CV) for each sampling point. The CV values were around 2%. The detection limit was 3.36 ng/ml and corresponded to three times the signal noise of the blank sample. The limit of quantification (LOQ) was 10.53 ng/ml. The chromatographic analysis indicated that the maximum concentrations of fluoxetine were reached at two hours post-administration (Akika Inu: 41.8 ± 0.6 ng/ml; German Shepherd: 45.3 ± 1.4.0 ng/ml), while the minimum concentrations were reached at 80 hours (Akika Inu: 3.9 ± 0.1 ng/ml; German Shepherd: 3.9 ± 0.1 ng/ml). A significant difference between breeds was only found in the values reached at 2 h post-administration (p<0.05). Results may indicate that due to the differences in the time curve, drug management might be different between phylogenetically different breeds.